La communication engageante au service des changements de comportement en matière d’éthique - Thomas Maxwell; Yanick Farmer (Communication)
One objective of an action-research conducted with managers of Montreal’s municipal administration is to test the effectiveness of the binding communication paradigm to promote the ethical behaviour. The authors wish to understand why regulatory policies based on written standards (codes of ethics) have failed to regulate behaviours and force managers to rethink their strategies. The proposed research focuses on individual commitment to produce significant changes.